The Characteristic of Care - Focused feminism values theory approached by Gilligan Through the female Character Nazneer in the Brick Lane ( 2007 ) - Divla Fadila Rahma (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri, 2023)
et,1/Mumtaz c.1